The Qur’ān and Woman’s Leadership Discourse in Indonesia: Modern Interpretation of QS. 4: 34 - Kusmana Kusmana (JOURNAL OF QUR'AN AND HADITH STUDIES, 2016)
The interpretation of QS. 4: 34 gains a new popularity in modern era as it has been used and abused as one of the references in discussing gender discourse in Islam. The paper discusses it in relation to woman’s leadership in modern Indonesian context. Hard-liners’ perceptions such as that of Salafi’s interpretation is excluded in this discussion. It deserves another adequate discussion.  The paper also restricts its discussion to the thoughts of Hamka, M. Quraish Shihab, Husein Muhammad, and of Ministry of Religious Affairs’ interpretation and treats them as exemplary of what is going on in the field of Qur’anic interpretation in this context. Using a descriptive-analytic method, this study deploys a library review technique in answering its question of the study, “how modern Muslim Indonesian scholars interpret the QS. 4: 34 in the context of democracy of Indonesia? The study concludes that they in deciphering the verse tend to adapt the demand of democracy but with a careful maintenance of the traditional wisdom.